Pengembangan Waqaf Temporer Bagi Pembangunan Ekonomi Umat: Suatu Kajian Penerapannya di Turki dan Indonesia - Hamdiah, Hamdiah; Husni Mubarrak; Iskandar Iskandar; Badrul Munir (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2024)
This article would like to discuss the issue of contemporary waqf (Islamic endowment) practices in the Islamic world today for the ummah economic empowerment and development by choosing Turkey and Indonesia as the focus of study. Among the contemporary issues of waqf that is attracting attention to be studied further regarding the Muslim community is the acceptance of its temporary waqf implementation, shifting from previous definition of waqf as almsgiving intended for a perpetual purpose. The selection of both countries is based on the large Muslim population, as well as representing different schools of thought (Indonesia with the Shafi'i school and Turkey with the Hanafi school). By using literature studies and interview with competent parties in the field of waqf purposively as the research method which are then analyzed synthetically, this article concludes that the existence of temporary waqf will develop in the future, as found in Turkey and in Indonesia, one of the reasons is for benefit, as well as the efficiency of the right to use the assets donated.